Re-visiting the Rhizosphere Eco-system for Agricultural Sustainability - Singh, Udai B.; Rai, Jai P.; Sharma, Anil K. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The present book entitled, "Re-visiting the Rhizosphere Eco-system for Agricultural Sustainability" written by experts in the field, provides a comprehensive and consolidated state-of art overview of various aspects of rhizosphere biology, ecology and functioning. The role of rhizosphere microbial diversity in enhancing plant health and plant-microbe beneficial symbioses is discussed. Main topics include the diversity of plant-associated microbes in the rhizosphere, below-ground communication among the plant, soil, insects and microbes, rhizosphere ecosystem functioning, rhizosphere engineering, recruitment of microorganisms in the rhizosphere, mycorrhizal fungal symbiosis, positive interaction of the plants with the beneficial soil microorganisms for inducing the plant growth, conferring abiotic and biotic stress tolerance and modulating several pathways of the plants for the proper establishment and revitalization in the degraded and contaminated soils or negative likes the host-pathogen interactions leading to the disease development in plants. Further chapters focus on the role of signaling during the different stages of the plant-microbe coexistence, in symbiotic or pathogenic relationships, in quorum sensing, microbial signaling and cross-talk, bio-film formation, and antimicrobial peptides. The book also discusses the application of microbes in biodegradation of xenobiotic contaminants, bioremediation of heavy metals, sustainable agriculture and soil health, biological control of insect pests and plant pathogens, and the latest tools of omics which offer pioneering approaches to the exploration of microbial structure and function, secretome, holobiome, below-ground interaction, and microbial cooperation for sustainable food production and enhanced resource acquisition. Descriptions of cutting-edge techniques and novel approaches make this book unique in the area of rhizosphere biology. This is a useful reading material for researchers and students of microbiology, agriculture, ecology, and rhizosphser studies.
Chapter 1. Evolution of the Knowledge and Practice of Endophytic Microorganisms for Enhanced Agricultural Benefit and Environmental Sustainability -- Chapter 2. The Mycorrhizosphere Revisited - Multitrophic Interactions -- Chapter 3. Conservation Strategies for Rhizobiome in Sustainable Agriculture -- Chapter 4. Exploring the rhizosphere microbiome for sustainable agriculture production -- Chapter 5. From Rhizosphere to Endosphere: Bacterial-Plant Symbiosis and its impact on Sustainable Agriculture -- Chapter 6. Arbuscular Mycorrhizal fungal symbiosis for mutual benefit: More than expectation -- Chapter 7. Rhizodeposits- An essential component for microbial interactions in rhizosphere -- Chapter 8. Rhizospheric Microbial Diversity: Organic Vs. Inorganic Farming System -- Chapter 9. Rhizomicrobes: The underground life for sustainable agriculture -- Chapter 10. Synthetic biology tools in cyanobacterial biotechnology: recent developments and opportunities -- Chapter 11. The potential of rhizobacteria for plant growth and stress adaptation -- Chapter 12. Mycoremediation - An emerging technology for mitigating environmental contaminants -- Chapter 13. Exploration of Plant growth-promoting rhizobacteria (PGPR) for improving productivity and soil fertility under sustainable agricultural practices -- Chapter 14. Rhizosphere engineering for systemic resistance/tolerance to biotic and abiotic stress -- Chapter 15. Understanding the Microbiome Interactions across the Cropping System -- Chapter 16. Role of rhizosphere microorganisms in endorsing overall plant growth and development -- Chapter 17. Rhizospheric microbial community as drivers of soil ecosystem: Interactive microbial communication and its impact on plants -- Chapter 18. Rhizospheric Microbes and Plant Health -- Chapter 19. Omics approaches to unravel the features of rhizospheric microbiome -- Chapter 20. Rhizo-deposit and their role in rhizosphere interactions among the plant, microbe and other ecological components for crop management -- Chapter 21. Effects of Irrigation with Municipal Wastewater on the Microbiome of the Rhizosphere of Agricultural Lands -- Chapter 22. Plant-Rhizosphereic microbes interactions: enhancing plant growth and improving soil biota -- Chapter 23. Microbes mediated rhizospheric engineering for salinity stress mitigation -- Chapter 24. Metatranscriptomics of plant rhizosphere: A promising tool to decipher the role of microorganisms in plant growth and development -- Chapter 25. Rhizospheric engineering for sustainable production of horticultural crops.
Keywords: Agricultural biotechnology; Subsistence farming; Agricultural genome mapping; Agricultural Biotechnology; Subsistence Agriculture; Agricultural Genetics